Komorbidität von Depression und Demenz bei geriatrischen Patienten mit akuter körperlicher Erkrankung - Hummel, Jana; Weisbrod, Cecilia; Bösch, Leila Magdalena; Himpler, Katharina; Diener, Slawomira; Gäbel, Andrea; Dipper, Lucy; Zieschang, Tania; Oster, Peter; Kopf, Daniel (Zeitschrift für Gerontologie und Geriatrie, 2012)
Geriatric patients with acute somatic illness have a high comorbidity of depression and dementia. The following differential diagnoses have to be discerned: pseudodementia in acute depressive states, depression as a risk factor for dementia, and a depressive episode in the early stage of dementia. For both the symptoms and the trigger factors of these differential diagnoses the overlap and the particularities were qualitatively examined in the AIDE-cog (Acute Illness and Depression in Elderly cognition) trial. A second prospective randomized controlled part of the AIDE-cog trial quantitatively evaluated the influence of cognitive impairment in geriatric patients with an acute somatic illness and comorbid depression on the therapeutic effect of cognitive behavioral therapy. A preliminary analysis shows that already in early dementia the therapeutic effects are inferior. Other psychotherapeutic methods that address the remaining cognitive and emotional functions in dementia must be evaluated.